Neutrophil Cathepsin G, but Not Elastase, Induces Aggregation of MCF-7 Mammary Carcinoma Cells by a Protease Activity-Dependent Cell-Oriented Mechanism. (2nd April 2014) - Yui, Satoru; Osawa, Yuuki; Ichisugi, Takeo; Morimoto-Kamata, Riyo
Abstract : We previously found that a neutrophil serine protease, cathepsin G, weakens adherence to culture substrates and induces E-cadherin-dependent aggregation of MCF-7 human breast cancer cells through its protease activity. In this study, we examined whether aggregation is caused by degradation of adhesion molecules on the culture substrates or through an unidentified mechanism. We compared the effect of treatment with cathepsin G and other proteases, including neutrophil elastase against fibronectin- (FN-) coated substrates. Cathepsin G and elastase potently degraded FN on the substrates and induced aggregation of MCF-7 cells that had been subsequently seeded onto the substrate. However, substrate-bound cathepsin G and elastase may have caused cell aggregation. After inhibiting the proteases on the culture substrates using the irreversible inhibitor phenylmethylsulfonyl fluoride (PMSF), we examined whether aggregation of MCF-7 cells was suppressed. PMSF attenuated cell aggregation on cathepsin G-treated substrates, but the effect was weak in cells pretreated with high concentrations of cathepsin G. In contrast, PMSF did not suppress cell aggregation on elastase-treated FN. Moreover, cathepsin G, but not elastase, induced aggregation on poly-L-lysine substrates which are not decomposed by these enzymes, and the action of cathepsin G was nearly completely attenuated by PMSF. These results suggest that cathepsin G induces MCF-7 aggregation through a cell-oriented mechanism.